2020
DOI: 10.21203/rs.2.24592/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What have we learnt from measles outbreaks in 3 English cities? A qualitative exploration of factors influencing vaccination uptake in Romanian and Roma Romanian communities

Abstract: Background: Since 2016, large scale measles outbreaks have heavily affected countries across Europe. In England, laboratory confirmed measles cases increased almost four-fold between 2017 and 2018, from 259 to 966 cases. Several of the 2017-18 measles outbreaks in England particularly affected Romanian and Roma Romanian communities, with the first outbreaks in these communities occurring in Birmingham, Leeds and Liverpool. This study explored factors influencing vaccination behaviours amongst Romanian and Roma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Specific barriers for European Roma were highlighted, with providers unaware of the difference between Roma and Romanian and lack of access to Romani-speaking interpreters. (36,55) Health professionals reported that the time allocated for vaccination appointments (10-15 minutes) was unrealistic when faced with communication barriers. (55) These barriers were mirrored at the system level in the lack of accessible, tailored or translated information about vaccination, available in different formats, for migrant populations.…”
Section: Barriers and Facilitators To Vaccine Uptake In Migrant Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific barriers for European Roma were highlighted, with providers unaware of the difference between Roma and Romanian and lack of access to Romani-speaking interpreters. (36,55) Health professionals reported that the time allocated for vaccination appointments (10-15 minutes) was unrealistic when faced with communication barriers. (55) These barriers were mirrored at the system level in the lack of accessible, tailored or translated information about vaccination, available in different formats, for migrant populations.…”
Section: Barriers and Facilitators To Vaccine Uptake In Migrant Populationsmentioning
confidence: 99%
“…(31,36,65) Fears of being charged for care or asked about immigration status, distrust of HCPs and authorities based on rumours or past experiences of discrimination, difficulties registering with a GP, or being refused care, were also highlighted. (7,31,36,(55)(56)(57)65) These fears were a major barrier to COVID-19 vaccination access in two UK studies of asylum seekers, refugees, and migrants with precarious immigration status, who expressed concern that they would be de-prioritised or excluded from the COVID-19 vaccine roll-out because of their status. (7,56) Migrants (n=10) interviewed after government announcements to widen COVID-19 vaccine access to undocumented migrants also remained unaware that they could be accessed free of charge and without immigration checks.…”
Section: Barriers and Facilitators To Vaccine Uptake In Migrant Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews for this study were limited to providers; however, in preceding studies, we have included Romanian and Roma community members to explore factors affecting vaccination uptake [27,30].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This study was undertaken in parallel with research we conducted with Romanian and Roma community members in Birmingham, Leeds and Liverpool to explore factors affecting vaccination at the time of the 2017/18 measles outbreaks. We found that factors related to access and acceptance, such as language and literacy barriers, ease of registering with a general practice (GP) and trust in health services, were the main barriers to vaccination amongst the communities [30]. The largest contributors to under-vaccination in the communities were due to access barriers, linked to social determinants, rather than community members' actively refusing vaccination.…”
Section: Introductionmentioning
confidence: 99%